Morphology and biogeography of Apiaceae subfamily Saniculoideae as inferred by phylogenetic analysis of molecular data - Calviño, C.I. (2008)
The phylogenetic placements of several African endemic genera at the base of Apiaceae subfamilies Saniculoideae and Apioideae have revolutionized ideas of relationships that affect hypotheses of character evolution and biogeography. Using an explicit phylogeny of subfamily Saniculoideae, we reconstructed the evolutionary history of phenotypic characters traditionally important in classification, identified those characters most useful in supporting relationships, and inferred historical biogeography. The 23 characters examined include those of life history, vegetative morphology, inflorescences, and fruit morphology and anatomy. These characters were optimized over trees derived from maximum parsimony analysis of chloroplast DNA trnQ-trnK sequences from 94 accessions of Apiaceae. The results revealed that many of these characters have undergone considerable modification and that traditional assumptions regarding character-state polarity are often incorrect. Infrasubfamilial relationships inferred by molecular data are supported by one to five morphological characters. However, none of these morphological characters support the monophyly of subfamilies Saniculoideae or Apioideae, the clade of Petagnaea, Eryngium and Sanicula, or the sister-group relationship between Eryngium and Sanicula. Southern African origins of Saniculoideae and of its tribes Steganotaenieae and Saniculeae are supported based on dispersal-vicariance analysis.